PENINGKATAN PERSEPSI KARYAWAN TERHADAP OBJEKTIVITAS PENILAIAN KINERJA MENGGUNAKAN METODE BARS DAN MBO - Purnamasari, Wulan; Ardhiyani, Ika Widya (Universitas Nahdlatul Ulama Surabaya, 2021)
The performance appraisal system in a company has an important role in achieving the target of achieving a job. Employee job satisfaction with the performance appraisal system depends on the level of employee perceptions of the performance appraisal system that applies to their workplace. This research was conducted in a company PT.X which is engaged in the BOPP film industry. The performance appraisal system in the company, based on employee perceptions, is still not effective. Here, the researcher attempted to design a performance appraisal system using the BARS and MBO methods. This research was conducted by means of field surveys, literature studies, and FGDs. The BARS and MBO methods are able to assess employee performance. Where in this method it creates unclear and measurable performance standards, there is no maximum feedback on the performance of employees, often the assessment is subjective, besides the assessment is carried out once a year so that it causes management to experience difficulties in monitoring. In addition, the company only dominantly assesses work activities and behavior, without assessing the work performance of each employee. Whereas here, the company should have carried out an objective performance appraisal, by having clear and measurable assessment standards and being able to provide feedback on employee performance achievements. Thus, researchers recommend using the BARS and MBO methods in the performance appraisal process. This aims to meet the company's needs for employee performance appraisals.